2020
DOI: 10.1186/s40560-020-00458-z
|View full text |Cite
|
Sign up to set email alerts
|

Early prediction of high flow nasal cannula therapy outcomes using a modified ROX index incorporating heart rate

Abstract: Background The ROX index (ratio of pulse oximetry/FIO2 to respiratory rate) has been validated to predict high flow nasal cannula therapy (HFNC) outcomes in patients with pneumonia. We evaluated a modified ROX index incorporating heart rate (HR) in patients initiated on HFNC for acute hypoxemic respiratory failure and as a preventative treatment following planned extubation. Methods We performed a prospective observational cohort study of 145 patients treated with HFNC. ROX-HR index was defined as the ratio o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
101
4
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(121 citation statements)
references
References 23 publications
11
101
4
5
Order By: Relevance
“…Preliminary data, mainly case reports and small case series, have also described its potential utility in patients with COVID-19 pneumonia [ 9 , 10 , [28] , [29] , [30] , [31] , [32] ], and usually in combination with awake proning [ 33 , 34 ]. The finding that ROX and mROX can be used as a prediction tool is also consistent with studies of early predictors of HFNO outcome in other forms of respiratory failure [ 19 , 20 ]. We found that ROX performed equivalently to mROX, and thus favoured it, as it comprised fewer input variables.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Preliminary data, mainly case reports and small case series, have also described its potential utility in patients with COVID-19 pneumonia [ 9 , 10 , [28] , [29] , [30] , [31] , [32] ], and usually in combination with awake proning [ 33 , 34 ]. The finding that ROX and mROX can be used as a prediction tool is also consistent with studies of early predictors of HFNO outcome in other forms of respiratory failure [ 19 , 20 ]. We found that ROX performed equivalently to mROX, and thus favoured it, as it comprised fewer input variables.…”
Section: Discussionsupporting
confidence: 83%
“…However, well-outlined protocolised provincial guidelines for intubation and mechanical ventilation, including score-based risk stratification (based on SOFA score, pre-morbid status, comorbidities and age) were followed [36] . Studies utilising composite physiological scores to determine predictors for the need for intubation inherently suffer from confirmation bias [ 19 , 20 , 37 , 38 ], as even if the ROX index is not formally calculated, the individual components (SpO 2 , FiO 2 and respiratory rate) are incorporated in a Bayesian-type reasoning by the clinician in making the intubation decision. Nevertheless, an objective measure that crystallises the current respiratory parameters, and can potentially reassure the clinician about the safety of continuing with HFNO, is still useful.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We believe that the biomarkers used in the COVID-IRS scores (respiratory rate, SaO2/FiO2 ratio, LDH, and either IL-6 or NLR), accurately represent relevant aspects of the clinical phenomena seen in severe COVID-19. Both, the respiratory rate and the SaO2/FiO2 ratio evaluate ventilatory function, whose deterioration is the main component associated with COVID-19 mortality [ 9 , 10 ]. The SaO2/FiO2 ratio was used as a surrogate for the PaO2/FiO2 ratio due to its availability and because it maintains a close linear relationship with O2-CO2 exchange and blood oxygenation [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the results of the machine algorithm, heart rate and PaO 2 are more important features than respiratory rate. In another study, heart rate was also used to modify the ROX index as a predictor of HFNC failure treatment [28]. And SpO 2 , instead of tidal volume, is a physiological parameter monitored routinely.…”
Section: Discussionmentioning
confidence: 99%